Transnational spaces - Jackson, Peter, 1955-; Crang, Phil, 1964-; Dwyer, Claire (Transnationalism. Routledge research in transnationalism., 2004)
This book takes an innovative perspective, looking at transnationalism as a social space that can be occupied by a wide range of actors, not all of whom are themselves directly connected to transnational migrant communities.